2018
DOI: 10.1007/s10439-018-2059-x
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements Evoked by Pulsed Infrared Radiation of the Rat Vestibular System

Abstract: Light at infrared wavelengths has been demonstrated to modulate the pattern of neural signals transmitted from the angular motion sensing semicircular canals of the vestibular system to the brain. In the present study, we have characterized physiological eye movements evoked by focused, pulsed infrared radiation (IR) stimuli directed at an individual semicircular canal in a mammalian model. Pulsed IR (1863 nm) trains were directed at the posterior semicircular canal in a rat using 200-400 µm optical fibers. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Activation of the targeted end organ-PC or AC-during either infrared or electrical stimulation was confirmed using eye movements (37,41) that were observed and recorded in some animals using a video-oculography system (ETL-200; ISCAN Inc., Figure 1B and lower traces in Figure 1C). The system located and tracked the center of the pupil and corneal reflections of both eyes.…”
Section: Eye Movementsmentioning
confidence: 83%
See 3 more Smart Citations
“…Activation of the targeted end organ-PC or AC-during either infrared or electrical stimulation was confirmed using eye movements (37,41) that were observed and recorded in some animals using a video-oculography system (ETL-200; ISCAN Inc., Figure 1B and lower traces in Figure 1C). The system located and tracked the center of the pupil and corneal reflections of both eyes.…”
Section: Eye Movementsmentioning
confidence: 83%
“…In the vestibular system, pulsed IR has been shown to rapidly alter the rate of transmitter release from inner ear hair cells and modulate the discharge rate of primary afferent fibers (34)(35)(36). In addition, our group recently reported that pulsed IR can be used to selectively activate the PC in anesthetized rats (37). In the present study, we measured eye movements, BP, HR, and heart rate variability (HRV) during unilateral pulsed IR stimulation of the PC or AC.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Spontaneous nystagmus scoring. Spontaneous nystagmus was recorded using a video eye-tracking system for rodents (ETL-200, ISCAN;Dyhrfjeld-Johnsen et al, 2013;Jiang and Rajguru, 2018). Spontaneous nystagmus with fast phase was scored with 6 -10 points, with 1 point for every 60 beats per minute (bpm; Bergquist et al, 2008;Günther et al, 2015).…”
Section: Drug Administration and Behavioral Assessmentmentioning
confidence: 99%